The development of a spatio-temporal model for water hyacinth, Eichhornia crassipes (Martius) Solms-Laubach (Pontederiaceae), biological control strategies - Van Schalkwyk, Helene (Stellenbosch : Stellenbosch University, 2016)
Thesis (MCom)--Stellenbosch University, 2016.